EFFECTIVENESS OF USING STUDENT CENTER LEARNING METHODS IN NURSING DEPARTMENT OF MANADO HEALTH POLYTECHNIC - Yourisna Pasambo; Semuel Tambuwun (Politeknik Kesehatan Makassar, 2019)
According to Priyatmojo dan Achmadi (2010), universities need to harmonize learning methods with the development of science and technology. To achieve this harmony, one effort that can be done is the use of the method student center learning (SCL) in learning. This study aims to determine the effectiveness of the use of student learning center methods in Nursing Department of Manado Health Polytechnic. This research is a quantitative study with a type of descriptive study. The research variable is the effectiveness of using the learning method student center learning (SCL). The population in this study were Manado Health Polytechnic Nursing Department students in D3 Class IA and IB who were exposed to the student center learning (SCL) learning method. The subject taking method uses the total sampling method. The effectiveness of using SCL methods was measured using a questionnaire which amounted to 20 statements and then the data were analyzed using SPSS 22.0. Based on the analysis of the data obtained, most of the research subjects 79 (90.8%) argued that the application of student center learning (SCL) in the Health Polytechnic Nursing Department was very effective. The results of this study indicate that the SCL teaching method is very effective in achieving learning objectives. This method not only makes students understand the material but also shapes their character. In addition to shaping the image that learning is fun and not boring, this method also builds the ability of students to actively participate in an activity. It was concluded that the student center learning learning (SCL) method was very effective applied in the Manado Health Polytechnic Department of Nursing. It is recommended that Manado Health Polytechnic institutions be able to provide training to lecturers on SCL learning methods. Keywords: effectiveness, student center learning, Nursing Department